Micromechanical property and stress analysis of fiber reinforced composite using finite element analysis (Simpsons Method) - Jha N.K.; Kumar S.; Tyagi A.; Jha D.K.; Jha C.S. (My University, 2025)
This work focusses on the influence of fiber and matrix geometry and fiber volume fraction on the elastic property of composite and their contributions towards shear property and tensile property of the GFRP composite. The stress analysis of different orientation and aspect ratio is being carried out to find the best design. Here micromechanics approach is applied by selecting RVE from the laminate. Python code and homogenization technique is implemented, which makes property calculation easier. The Classical lamination theory is implemented for stress analysis and validating with Finite Element Analysis value. The FEA(abaqus) is used for calculation of property and stress analysis. In case of longitudinal youngs modulus the effect of geometry of fiber and matrix are negligible. In case of Transverse youngs modulus the effect of geometry of fiber and matrix are there. SM-SF > SM-CF > HM-CF. The computational result is validated by the various analytical approach to achieve the best property and there is negligible error found between the result. It seems to be GFRP composite is most effective if load is acting along the direction of fiber. Further if all analytical methods are compared than Nielsen elastic model showing large variation not acceptable after 60% volume fraction. The analysis shows that different type of geometry and size variation method can be used for the property enhancement of the composite material and the CLT is used for stress analysis. The enhancement in shear and transverse property mostly applied in the manufacturing/design of shell structure in the industries and different engineering field. © 2021 Elsevier Ltd. All rights reserved